Moldova Policy Notes 2021 : Sectoral Recommendations - World Bank (World Bank, Washington, DC, 2022)
Moldova’s policy priorities and key actions going forward: Strengthening the capacity and governance of public administration; Strengthening the judiciary and the fight against corruption; Supporting a resilient recovery while safeguarding fiscal sustainability; Building fiscal resilience at the subnational level with land administration and property registration and valuation; Enhancing labor markets and addressing COVID-19 challenges; Achieving a sustainable social protection system; Improving the efficiency and resilience of health service delivery; Strengthening environment protection and disaster risk management; Water resource management; Increasing resilience and competitiveness of agriculture; Enhancing the business environment and market competition; Fostering SMEs and strengthening FDI linkages; Enhancing financial sector stability and governance; Strengthening education outcomes and skills; Expanding inclusive digital development opportunities; Multimodal transport and logistics; and Addressing energy security and sustainability.